What can we learn about monetary policy transparency from financial market data? - Roger Courtenay; Andrew Clare (Deutsche Bundesbank, 2001)
In this paper we investigate the impact of UK macroeconomic news announcements on selected futures contracts and exchange rates. We include a wide set of scheduled public news announcements in our study, including official interest rate decisions. We investigate whether the reaction to these announcements has changed since the Bank of England was granted operational independence in May 1997. Our results indicate that there may well have been changes in the way that financial markets incorporate key economic data into securities prices. In particular, we document an increase in the speed of the reaction to interest rate announcements, but also some evidence of a fall in the size of the full reaction. – – In diesem Papier wird untersucht, wie in Großbritannien makroökonomische Neuigkeiten auf ausgewählte Terminkontrakte und Wechselkurse wirken. In der Studie wird eine breite Palette regelmäßig veröffentlichter Daten betrachtet, einschließlich der Entscheidungen über die Notenbankzinsen. Wir untersuchen, ob die Reaktionen auf diese Ankündigungen sich geändert haben, seit der Bank von England im Mai 1997 operationelle Unabhängigkeit gewährt worden ist. Die Ergebnisse zeigen, dass durchaus Veränderungen zu verzeichnen sind in der Art und Weise, wie auf den Finanzmärkten ökonomische Daten die Wertpapierpreise ändern. Insbesondere dokumentieren wir, dass die Reaktionen auf Zinsänderungen schneller erfolgen aber auch, dass die Stärke der Reaktionen geringer ist.
Keywords: 330